2004
DOI: 10.1021/jo049757p
|View full text |Cite
|
Sign up to set email alerts
|

Endo-Selective Quenching of Hexahydropyrrolo[2,3-b]indole-Based N-Acyliminium Ions

Abstract: Radical decarboxylation of L-tryptophan-derived (2S,3aR,8aS)-8-arylsulfonyl-1,2-di(methoxycarbonyl)-1,2,3,3a,8,8a-hexahydro-2H-pyrrolo[2,3-b]indoles 8 and 9 in the presence of diphenyl diselenide results in the endo-selective formation of (2R,3aR,8aS)-8-arylsulfonyl-1-methoxycarbonyl-2-phenylselenyl-1,2,3,3a,8,8a-hexahydro-2H-pyrrolo[2,3-b]indoles 10 and 11. These selenides, in conjunction with Lewis acids, serves as precursors to the corresponding N-acyl iminium ions, which undergo selective endo-face quenchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
(38 reference statements)
3
7
0
Order By: Relevance
“…With an unsubstituted C2 radical and a bulky trap such as diphenyl disulfide, or diphenyl diselenide, almost complete selectivity was obtained for reaction on the endo surface, as in the formation of 109 and 110. 68,69 The stereochemistry of 109 and 110 was readily apparent from the 1 H-NMR coupling motifs, which followed the pattern previously established, and was confirmed by X-ray crystallographic analysis of 110. 68 Radical decarboxylation with trapping by methyl acrylate, 69 leading to the formation of 111, was also highly endo-selective (13:1).…”
Section: Scheme 1 Alkylation With Retention Of Configurationsupporting
confidence: 74%
See 1 more Smart Citation
“…With an unsubstituted C2 radical and a bulky trap such as diphenyl disulfide, or diphenyl diselenide, almost complete selectivity was obtained for reaction on the endo surface, as in the formation of 109 and 110. 68,69 The stereochemistry of 109 and 110 was readily apparent from the 1 H-NMR coupling motifs, which followed the pattern previously established, and was confirmed by X-ray crystallographic analysis of 110. 68 Radical decarboxylation with trapping by methyl acrylate, 69 leading to the formation of 111, was also highly endo-selective (13:1).…”
Section: Scheme 1 Alkylation With Retention Of Configurationsupporting
confidence: 74%
“…68,69 The stereochemistry of 109 and 110 was readily apparent from the 1 H-NMR coupling motifs, which followed the pattern previously established, and was confirmed by X-ray crystallographic analysis of 110. 68 Radical decarboxylation with trapping by methyl acrylate, 69 leading to the formation of 111, was also highly endo-selective (13:1).…”
Section: Scheme 1 Alkylation With Retention Of Configurationsupporting
confidence: 74%
“…A decrease in the ground-state energy of the oxocarbenium ion intermediate due to resonance stabilization from the C-1 phenyl substituent should decrease the rates of nucleophilic addition to the oxocarbenium ions 9a and 9b (k a and k b , Scheme 3) but not affect the rate of nucleophile diffusion between the two diastereotopic faces (k diffusion , Scheme 3). Highly selective additions of Me 3 SiCN to stabilized electrophiles such as N-acyliminium ions 38,39 and other benzylic oxocarbenium ions have also been observed. 40 A competition experiment demonstrated that the disparity between the diastereoselectivities obtained from the additions of allyltrimethylsilane and Me 3 SiCN to oxocarbenium ions lacking the stabilizing phenyl substituents may result from the higher relative reactivity of Me 3 SiCN.…”
Section: Resultsmentioning
confidence: 95%
“…A decrease in the ground-state energy of the oxocarbenium ion intermediate due to resonance stabilization from the C-1 phenyl substituent should decrease the rates of nucleophilic addition to the oxocarbenium ions 9a and 9b ( k a and k b , Scheme ) but not affect the rate of nucleophile diffusion between the two diastereotopic faces ( k diffusion , Scheme ). Highly selective additions of Me 3 SiCN to stabilized electrophiles such as N -acyliminium ions , and other benzylic oxocarbenium ions have also been observed
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation